Protein Kinase Cβ(II)-Mediated Phosphorylation of Endothelial Nitric Oxide Synthase Threonine 495 Mediates the Endothelial Dysfunction Induced by FK506 (Tacrolimus) - Chiasson, Valorie L. (The American Society for Pharmacology and Experimental Therapeutics, 2011)
FK506 [tacrolimus; hexadecahydro-5,19-dihydroxy-3-[2-(4-hydroxy-3-methoxycyclohexyl)-1-methylethenyl]-14,16-dimethoxy-4,10,12,18-tetramethyl-8-(2-propenyl)-15,19-epoxy-3H-pyrido[2,1-c][1,4]oxa-azacyclotricosine-1,7,20,21(4H,23H)-tetrone] is used clinically to reduce the incidence of allograft rejection; however, chronic administration leads to endothelial dysfunction and hypertension. We have previously shown that FK506 activates Ca(2+)/diacylglycerol-dependent conventional protein kinase C (cPKC), which phosphorylates endothelial nitric oxide synthase (eNOS) at one of its inhibitory sites, Thr495. However, which cPKC isoform is responsible for phosphorylating eNOS Thr495 is unknown. The aim of the current study was to determine the cPKC isoform that is activated by FK506, leading to decreased endothelial function. FK506 reduced endothelium-dependent relaxation responses, yet had no effect on endothelium-independent relaxation responses in aortas from control mice. Of the various cPKC isoforms, only the administration of a PKCβ(II) isoform-specific peptide inhibitor restored aortic relaxation responses to that of controls. In aortic endothelial cells, FK506 significantly increased PKCβ(II) activation compared with vehicle-treated controls, and this was prevented by a PKCβ(II) isoform-specific peptide inhibitor. In addition, a PKCβ(II) isoform-specific peptide inhibitor prevented the increase in eNOS Thr495 phosphorylation induced by FK506. Taken together, our results indicate that β(II) is the cPKC isoform responsible for phosphorylating eNOS at the inhibitory site Thr495 in response to FK506. PKCβ(II) inhibition could prove beneficial in ameliorating the endothelial dysfunction and hypertension in patients treated with FK506.